Primary Thyroid-Like Follicular Renal Cell Carcinoma: An Emerging Entity - S. Malde; I. Sheikh; I. Woodman; D. Fish; P. Bilagi; M. K. M. Sheriff (Case Reports in Pathology)
Primary thyroid-like follicular carcinoma of the kidney is a rare but newly emerging histological variant of renal cell carcinoma RCC, with only nine cases reported in the literature to date. We present a further case of this unique condition, discuss the workup and typical histological findings, and review the literature regarding this rare histological variant.